Proteome of the testicular cell-conditioned medium supports germ cell differentiation in vitro - Prasetyaningtyas, Wahono Esthi; Karja, Ni Wayan Kurniani; Agungpriyono, Srihadi; Adnyane, I Ketut Mudite; Mohamad, Kusdiantoro; Fahrudin, Mokhamad (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study aimed to evaluate the effect of testicular cell conditioned medium (TCCM) on in vitro male germ cell differentiation and provide a proteomic profile of TCCM. Materials and Methods: TCCM was collected from 5-day-old mouse testicular tissues cultured in serum-free DMEM. Proteomic analysis was performed using liquid chromatography–tandem mass spectrometry. Germ cells were isolated from 13.5 days post-coitum (dpc) mouse fetal genital ridges and divided into three groups: (a) control (DMEM + 15% FCS), (b) 40% TCCM + 60% DMEM + 15% FCS, and (c) 60% TCCM + 40% DMEM + 15% FCS. Cells were cultured for 24 days. Gene expression of Oct4, Acr, Dazl, Vasa, Stra8, Prm1, and Gdf9 was measured using real-time PCR. Results: Proteomic analysis identified 26 proteins in TCCM. Notably, COL4A1, COL4A2, and HSPG2 are associated with the basement membrane and are essential for supporting extracellular matrix integrity, while FN1, FBN1, COL1A1, COL1A2, COL5A2, and COL3A12 are linked to the PI3K-AKT pathway, which regulates cell proliferation. In TCCM-treated groups, germ cells differentiated into spermatid-like cells by day 18 and sperm-like structures by day 24. Oct4, Dazl, Vasa, Stra8, Prm1, and Acr were expressed across all groups, but without statistically significant differences (p > 0.05), while Gdf9 was not expressed. Conclusion: The addition of TCCM, which contains extracellular matrix (ECM) proteins, enhanced in vitro differentiation of male germ cells into sperm-like structures, together with somatic cells from the genital ridge. These ECM proteins contribute to creating a microenvironment that closely mimics in vivo conditions. J. Adv. Vet. Anim. Res., 12(4): 1087–1096, December 2025 http://doi.org/10.5455/javar.2025.l969